MODEL LAPS (LOGAN AVENUE PROBLEM SOLVING)-HEURISTIC BERBASIS CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA - Alibas, Fadhila; Agung, Afiq; Hutapea, Bilferi (Jurnal Pendidikan Fisika FKIP UM Metro, 2025)
One of the most important skills to be mastered by students in the rapid development of 21st century technology is the ability to solve problems. One of the innovations in improving students' problem-solving abilities is the implementation of the LAPS-Heuristic Based on CRT model. This study aims to describe the effect of the CRT-Based LAPS Heuristic learning model on students' physics problem-solving abilities. This type of research is a quasi-experimental study with a "pretest-posttest non-equivalent control group design" research design. The data collection instrument used in this study was a test of students' physics problem-solving abilities. Descriptive statistical analysis and inferential statistical analysis were used in analyzing the research data. Independent sample t-test analysis was set to test the inferential statistical analysis in the study. The results of this study concluded that there was an effect on students' problem-solving abilities who applied the CRT-Based LAPS Heuristic learning model. The average physics problem-solving ability of students with the CRT-Based LAPS Heuristic learning model was 77.69, higher than that of the direct LAPS Heuristic model of 74.65. The results of this study conclude that the CRT-LAPS Heuristic is very suitable for application learning in high school to improve students' physics problem-solving abilities.